Reproductive biology and gestation of the male seahorse, Hippocampus barbouri (Jordan and Richardson 1908) - Oconer, Edna Perez 1960- (2002)
Seahorse, Hippocampus barbouri (Jordan-Richardson 1908) is one of the endangered species worldwide. Attempts to breed the fish in captivity are hampered by many unanswered questions regarding its general reproductive biology especially its gestation. This study is the first investigation of the gross morphology of reproductive system, histology and ultrastructure of the brood pouch, and localization of sex steroids through immunohistochemistry and enzyme histochemistry. Results showed that seahorse reproductive system does not differ from a typical male teleost except for the presence of brooding pouch in males and was evident starting 8 cm length. The seahorse testis does not form spermatocyst and belongs to unrestricted spermatogonial type. Onset of sex differentiation was observed at size length 4 to 6 cm. Ultrastructuctural study revealed the absence of structural connection between the embryo and thecapsules formed by the pouch wall. Immunohistochemistry, enzyme histochemistry and chemiluminescence studies showed synthesis of the steroids, estrogen and progesterone in the testes, brood pouch and interrenal gland and their possible involvement in gestation by their abundance during gestation. These findings will be valuable in the aquaculture and conservation of this species.